Examples with solutions for Negative Exponents: Presenting powers in the denominator as powers with negative exponents

Exercise #1

1123=? \frac{1}{12^3}=\text{?}

Video Solution

Step-by-Step Solution

To begin with, we must remind ourselves of the Negative Exponent rule:

an=1an a^{-n}=\frac{1}{a^n} We apply it to the given expression :

1123=123 \frac{1}{12^3}=12^{-3} Therefore, the correct answer is option A.

Answer

123 12^{-3}

Exercise #2

Insert the corresponding expression:

152= \frac{1}{5^2}=

Video Solution

Step-by-Step Solution

To solve the given problem, we need to express 152 \frac{1}{5^2} using negative exponents. We'll apply the formula for negative exponents, which is 1an=an \frac{1}{a^n} = a^{-n} :

  • Identify the base and power in the denominator. Here, the base is 5 5 and the power is 2 2 .
  • Apply the inverse formula: 152=52 \frac{1}{5^2} = 5^{-2} .

Thus, the equivalent expression for 152 \frac{1}{5^2} using a negative exponent is 52 5^{-2} .

Answer

52 5^{-2}

Exercise #3

Insert the corresponding expression:

142= \frac{1}{4^2}=

Video Solution

Step-by-Step Solution

To solve the problem of expressing 142\frac{1}{4^2} using powers with negative exponents:

  • Identify the base in the denominator: 4 raised to the power 2.
  • Apply the rule for negative exponents that states 1an=an\frac{1}{a^n} = a^{-n}.
  • Express 142\frac{1}{4^2} as 424^{-2}.

Thus, the expression 142\frac{1}{4^2} can be rewritten as 42 4^{-2} .

Answer

42 4^{-2}

Exercise #4

Insert the corresponding expression:

132= \frac{1}{3^2}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll use the rule of negative exponents:

  • Step 1: Identify that the given expression is 132\frac{1}{3^2}.
  • Step 2: Recognize that 132\frac{1}{3^2} can be rewritten using the negative exponent rule.
  • Step 3: Apply the formula 1an=an\frac{1}{a^n} = a^{-n} to the expression 132\frac{1}{3^2}.

Now, let's work through these steps:

Step 1: We have 132\frac{1}{3^2} where 3 is the base and 2 is the exponent.

Step 2: Using the formula, convert the denominator 323^2 to 323^{-2}.

Step 3: Thus, 132=32\frac{1}{3^2} = 3^{-2}.

Therefore, the solution to the problem is 323^{-2}.

Answer

32 3^{-2}

Exercise #5

Insert the corresponding expression:

167= \frac{1}{6^7}=

Video Solution

Step-by-Step Solution

To solve this problem, we will rewrite the expression 167\frac{1}{6^7} using the rules of exponents:

Step 1: Identify the given fraction.

We start with 167\frac{1}{6^7}, where the base in the denominator is 6, and the exponent is 7.

Step 2: Apply the formula for negative exponents.

The formula an=1ana^{-n} = \frac{1}{a^n} allows us to rewrite a reciprocal power as a negative exponent. This means the expression 167\frac{1}{6^7} can be rewritten as 676^{-7}.

Step 3: Conclude with the answer.

By transforming 167\frac{1}{6^7} to its equivalent form using negative exponents, the expression becomes 676^{-7}.

Therefore, the correct expression is 67\boxed{6^{-7}}, which corresponds to choice 2 in the given options.

Answer

67 6^{-7}

Exercise #6

Insert the corresponding expression:

1202= \frac{1}{20^2}=

Video Solution

Step-by-Step Solution

To solve this problem, we will use the properties of exponents. Specifically, we will convert the expression 1202 \frac{1}{20^2} into a form that uses a negative exponent. The general relationship is that 1an=an \frac{1}{a^n} = a^{-n} .

Applying this rule to the given expression:

  • Step 1: Identify the current form, which is 1202 \frac{1}{20^2} .
  • Step 2: Apply the negative exponent rule: 1202=202 \frac{1}{20^2} = 20^{-2} .
  • Step 3: This expression, 202 20^{-2} , represents 1202 \frac{1}{20^2} using a negative exponent.

Therefore, the expression 1202 \frac{1}{20^2} can be expressed as 202 20^{-2} , which aligns with choice 1.

Answer

202 20^{-2}

Exercise #7

183=? \frac{1}{8^3}=\text{?}

Video Solution

Step-by-Step Solution

We use the negative exponent rule.

bn=1bn b^{-n}=\frac{1}{b^n}

We apply it to the problem in the opposite sense.:

183=83 \frac{1}{8^3}=8^{-3}

Therefore, the correct answer is option A.

Answer

83 8^{-3}

Exercise #8

129=? \frac{1}{2^9}=\text{?}

Video Solution

Step-by-Step Solution

We use the power property for a negative exponent:

an=1an a^{-n}=\frac{1}{a^n} We apply it to the given expression:

129=29 \frac{1}{2^9}=2^{-9}

Therefore, the correct answer is option A.

Answer

29 2^{-9}

Exercise #9

2738=? \frac{27}{3^8}=\text{?}

Video Solution

Step-by-Step Solution

First, let's note that 27 is a power of the number 3:

27=33 27=3^3 Using this fact gives us a situation where in the fraction's numerator and denominator we get terms with identical bases, let's apply this to the problem:

2738=3338 \frac{27}{3^8}=\frac{3^3}{3^8} Now let's recall the law of exponents for division between terms without identical bases:

aman=amn \frac{a^m}{a^n}=a^{m-n} Let's apply this law to the last expression we got:

3338=338=35 \frac{3^3}{3^8}=3^{3-8}=3^{-5} where in the first stage we applied the above law and in the second stage we simplified the expression we got in the exponent,

Let's summarize the solution steps, we got:

2738=3338=35 \frac{27}{3^8}=\frac{3^3}{3^8}=3^{-5} Therefore the correct answer is answer D.

Answer

35 3^{-5}

Exercise #10

1(2)7=? \frac{1}{(-2)^7}=?

Video Solution

Step-by-Step Solution

To begin with we deal with the expression in the denominator of the fraction. Making note of the power rule for exponents (raising an exponent to another exponent):

(am)n=amn (a^m)^n=a^{m\cdot n} We obtain the following:

(2)7=(12)7=(1)727=127=27 (-2)^7=(-1\cdot2)^7=(-1)^7\cdot2^7=-1\cdot2^7=-2^7

We then return to the initial problem and apply the above information:

1(2)7=127=11127=127 \frac{1}{(-2)^7}=\frac{1}{-2^7}=\frac{1}{-1}\cdot\frac{1}{2^7}=-\frac{1}{2^7}

In the last step we remember that:

11=1 \frac{1}{-1}=-1

Next, we remember the Negative Exponent rule ( raising exponents to a negative power)

an=1an a^{-n}=\frac{1}{a^n} We apply it to the expression we obtained in the last step:

127=27 -\frac{1}{2^7}=-2^{-7} Let's summarize the steps of the solution:

1(2)7=127=27 \frac{1}{(-2)^7}=-\frac{1}{2^7} = -2^{-7}

Therefore, the correct answer is option C.

Answer

(2)7 (-2)^{-7}

Exercise #11

1an=? \frac{1}{a^n}=\text{?}

a0 a\ne0

Video Solution

Step-by-Step Solution

This question is actually a proof of the law of exponents for negative exponents, we will prove it simply using two other laws of exponents:

a. The zero exponent law, which states that raising any number to the power of 0 (except 0) will give the result 1:

X0=1 X^0=1

b. The law of exponents for division between terms with identical bases:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n}

Let's return to the problem and pay attention to two things, the first is that in the denominator of the fraction there is a term with base a a and the second thing is that according to the zero exponent law mentioned above in a' we can always write the number 1 as any number (except 0) to the power of 0, particularly in this problem, given that a0 a\neq0 we can claim that:

1=a0 1=a^0

Let's apply this to the problem:

1an=a0an \frac{1}{a^n}=\frac{a^0}{a^n}

Now that we have in the numerator and denominator of the fraction terms with identical bases, we can use the law of division between terms with identical bases mentioned in b' in the problem:

a0an=a0n=an \frac{a^0}{a^n}=a^{0-n}=a^{-n}

Let's summarize the steps above, we got that:

1an=a0an=an \frac{1}{a^n}=\frac{a^0}{a^n}=a^{-n}

In other words, we proved the law of exponents for negative exponents and understood why the correct answer is answer c.

Answer

an a^{-n}

Exercise #12

242=? \frac{2}{4^{-2}}=\text{?}

Video Solution

Step-by-Step Solution

First, let's note that 4 is a power of 2:

4=22 4=2^2 therefore we can perform a conversion to a common base for all terms in the problem,

Let's apply this:

242=2(22)2 \frac{2}{4^{-2}}=\frac{2}{(2^2)^{-2}} Next, we'll use the power law for power of power:

(am)n=amn (a^m)^n=a^{m\cdot n} and we'll apply this law to the denominator term we got in the last step:

2(22)2=222(2)=224 \frac{2}{(2^2)^{-2}}=\frac{2}{2^{2\cdot(-2)}}=\frac{2}{2^{-4}} where in the first step we applied the above law to the denominator and in the second step we simplified the expression we got,

Next, we'll use the power law for division between terms with identical bases:

aman=amn \frac{a^m}{a^n}=a^{m-n} and we'll apply this law to the last expression we got:

224=21(4)=21+4=25 \frac{2}{2^{-4}}=2^{1-(-4)}=2^{1+4}=2^5

Therefore the correct answer is answer B.

Answer

242 2\cdot4^2

Exercise #13

10(5)3=? \frac{10}{(-5)^3}=\text{?}

Video Solution

Step-by-Step Solution

First, let's note that:

a.

10=52 10=5\cdot2

For this, we'll recall the law of exponents for multiplication in parentheses:

(ab)n=anbn (a\cdot b)^n=a^n\cdot b^n

According to this, we get that:

(5)3=(15)3=(1)353=153=53 (-5)^3=(-1\cdot5)^3=(-1)^3\cdot5^3=-1\cdot5^3=-5^3

We want to use the understanding in 'a' to get terms with identical bases in the numerator and denominator,

Let's return to the problem and apply the understandings from 'a' and 'b':

10(5)3=2553=21553=2553 \frac{10}{(-5)^3}=\frac{2\cdot5}{-5^3}=\frac{2}{-1}\cdot\frac{5}{5^3}=-2\cdot\frac{5}{5^3}

Where in the first stage we used 'a' in the numerator and 'b' in the fraction's denominator, in the next stage we presented the fraction as a multiplication of fractions according to the rule for multiplying fractions, then we simplified the first fraction in the multiplication.

Now we'll use the law of exponents for division between terms with identical bases:

aman=amn \frac{a^m}{a^n}=a^{m-n}

Let's apply this law to the expression we got:

2553=2513=252 -2\cdot\frac{5}{5^3}=-2\cdot5^{1-3}=-2\cdot5^{-2}

where in the first stage we applied this law to the fraction in the multiplication and then simplified the expression we got,

Let's summarize the solution steps:

10(5)3=2553=252 \frac{10}{(-5)^3} =-2\cdot\frac{5}{5^3} =-2\cdot5^{-2}

Therefore, the correct answer is answer b.

Answer

2(5)2 -2(-5)^{-2}